Bacteriological profile of burn patients in a tertiary care center – Changing pattern - Sunil Sharma; Raman Tandon; Dharmala Nitesh Reddy; Nemi Chand (Indian Journal of Burns, 2023)
Background: Burn is a devastating injury; burn patients are at high risk of developing hospital-acquired infections. Routine monitoring of bacterial infection and antimicrobial susceptibility of these microorganisms can help us select appropriate antibiotics to save lives. Materials and Methods: A prospective study was done on burn patients admitted to the Department of Burns, Plastic and Maxillofacial Surgery. A total of 300 patients were studied and followed up for wound swabs, laboratory tests, and clinical features on the 2nd, 4th, 8th, and 14th postburn days. Organisms’ prevalent and antibiotic sensitivities at those particular periods were determined. The thermal burn patients presenting within 24 h of all age groups admitted were included. Electrical, chemical, and radiation burns and all those who were not willing to participate in the study were excluded. Results: The most common organisms identified in our study were Pseudomonas, Acinetobacter, and Klebsiella species. Meropenem, imipenem, and piperacillin + tazobactam were the antibiotics to which the organisms were most sensitive. Conclusion: In order to manage infections and decrease overall morbidity and mortality, it is essential to identify the changing trends in microbial infection in burn wounds by wound swab culture and administering antibiotics as per their sensitivity patterns. Pseudomonas, Acinetobacter, and Klebsiella species were the most isolated organisms, which were highly sensitive to carbapenems, piperacillin + tazobactam, netilmicin, and colistin. The cultural report also shows pan-resistant organisms. This factor must be considered while advising antibiotics at the time of admission. More attention needs to be paid to the increasing multidrug resistance rates of Acinetobacter species.